1982
DOI: 10.3758/bf03206217
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of 1 week’s monocular exposure to long-wavelength stimuli

Abstract: Subjects wore a long-wavelength passband filter over one eye for 1 week. As a consequence, for that eye only, sensitivity to long-wavelength stimuli declined, unique yellow shifted to longer wavelengths, and scotopic stimuli acquired a strikingly bluish appearance. These results make it very likely that long-term exposure to a long-wavelength world can induce relatively prolonged (at least hours) postreceptoral adaptation.There have been many studies of the visual system's response to restricted environments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Hypoxia decreases the maximum response rate of all cone pathways equally; however, as the number of S cones is limited, their absolute responses might become undetectable at earlier stages compared with the more redundant L or M cones 24. While hypoxia-induced cone dysfunction is likely to be the cause for decreased colour vision, other factors may play a role: the use of sunglasses required to prevent high-altitude UV light damage may result in a long-lasting chromatic adaptation to middle- and long-wavelength stimuli, which in turn may attenuate the potential effects on deutan and protan at high altitude 25 26. Indeed, it would be important to rigorously investigate the existence and mechanism(s) of adaptation of chromatic threshold due to the prolonged stay at high altitude in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia decreases the maximum response rate of all cone pathways equally; however, as the number of S cones is limited, their absolute responses might become undetectable at earlier stages compared with the more redundant L or M cones 24. While hypoxia-induced cone dysfunction is likely to be the cause for decreased colour vision, other factors may play a role: the use of sunglasses required to prevent high-altitude UV light damage may result in a long-lasting chromatic adaptation to middle- and long-wavelength stimuli, which in turn may attenuate the potential effects on deutan and protan at high altitude 25 26. Indeed, it would be important to rigorously investigate the existence and mechanism(s) of adaptation of chromatic threshold due to the prolonged stay at high altitude in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…These have revealed longer-term aftereffects that may emerge only after sustained periods of adaptation. For example, long-term exposure to a colored bias induces aftereffects that are much more persistent than short-term chromatic adaptation (Neitz et al, 2002, Belmore and Shevell, 2010, Eisner and Enoch, 1982), and color vision in cataract patients requires months to readapt after surgery (Delahunt et al, 2004). Similarly, while brief adaptation to blur or contrast is sufficient to induce a strong perceptual aftereffect, hours of exposure are required to see increases in acuity and sensitivity (Mon-Williams et al, 1998, Kwon et al, 2009, Zhang et al, 2009).…”
Section: Timescalesmentioning
confidence: 99%
“…A recent study found that the aftereffects show two independent time courses, a brief decay over seconds similar to the dynamics measured for contrast adaptation and an essentially static bias that requires exposure to a new pattern to reset (Vul, Krizay, & MacLeod, 2008). Long-term color aftereffects can also be induced when observers are exposed for a few hours a day to color-biased environments created by changing the spectrum of the room lighting, wearing tinted contacts, or viewing colored edges on a display (Belmore & Shevell, 2008, 2010; Eisner & Enoch, 1982; Neitz, Carroll, Yamauchi, Neitz, & Williams, 2002). Exposure to a red context shifts the wavelength that appears unique yellow, and these aftereffects can persist for days.…”
Section: The Timescales Of Adaptationmentioning
confidence: 99%